Myricetin Induces Autophagy and Cell Cycle Arrest of HCC by Inhibiting MARCH1-Regulated Stat3 and p38 MAPK Signaling Pathways - Yang, Wei; Su, Jiaqi; Li, Mingjing; Li, Tiantian; Wang, Xu; Zhao, Mingdong; Hu, Xuemei (Frontiers in Pharmacology, 2021)
Myricetin is a type of natural flavonol known for its anti-cancer activity. However, the molecular mechanism of myricetin in anti-hepatocellular carcinoma (HCC) is not well-defined. Previous studies indicated that down-regulation of membrane-associated RING-CH finger protein 1 (MARCH1) is contributed to treatment of a variety of cancers. Whether the anti-cancer property of myricetin is associated with MARCH1 expression remains to be investigated. This study explored the anti-HCC mechanism of myricetin. Our results indicate that myricetin induces autophagy and arrests cell cycle at G2/M phase to suppress proliferation of HCC cells by down-regulating MARCH1. Myricetin reduces MARCH1 protein in Hep3B and HepG2 cells. Interestingly, myricetin up-regulates MARCH1 mRNA level in Hep3B cells but down-regulates it in HepG2 cells. Knockdown of MARCH1 by siRNAs (small interfering RNAs) decreases the phosphorylated p38 MAPK (p-p38 MAPK) and Stat3 (p-Stat3), and inhibits HCC cells viability. Moreover, myricetin inhibits p38 MAPK and Stat3 signaling pathway by down-regulating MARCH1 to repress HCC growth both in vitro and in vivo. Bafilomycin A1 (BafA1), a autophagy inhibitor, has synergetic effect with myricetin to inhibit HCC growth. Taken together, our results reveal that myricetin inhibits proliferation of HCC cells by inhibiting MARCH1-regulated p38 MAPK and Stat3 signaling pathway. This study provides a new molecular mechanism for myricetin in anti-HCC and suggests that targeting MARCH1 could be a novel treatment strategy in developing anticancer therapeutics.